Peningkatan Motivasi dan Prestasi Belajar Matematika melalui Pendekatan Pendidikan Matematika Realistik Indonesia di MI Yappi Bansari - Purwanti (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve students' motivation and learning achievement in mathematics subjects through the Indonesian Realistic Mathematics Education (PMRI) approach. The study used class action methods including planning, implementation, observation, and reflection. The subject of the study was grade IV student MI Yappi Bansari in the 2019/2020 school year. The results of the implementation of PMRI approach are obtained through tests and questionnaires. The results showed that the increase in the replay score in cycle I averaged the student's replay score at a percentage of 72%. In the improvement of Cycle II learning there was a significant increase of 83%. Indonesia's Realistic Mathematics Education (PMRI) approach can improve math learning achievement and can be applied to grade IV elementary school/ MI.